Sflt-1 in heart failure: relation with disease severity and biomarkers. (3rd July 2016) - Gruson, Damien; Hermans, Michel P.; Ferracin, Benjamin; Ahn, Sylvie A.; Rousseau, Michel F.
Abstract: Soluble fms-like tyrosine kinase-1 (sFlt-1) is an endogenous inhibitor of endothelial growth factors, such as placental growth factor (PlGF), which modulates cardiovascular (CV) remodeling. We determine sFlt-1 levels in patients with heart failure (HF) and its relationship to adverse cardiovascular (CV) events and biomarkers of cardiovascular risk. Levels of sFlt-1 and PlGF levels were also determined in healthy volunteers and patients with type 2 diabetes mellitus (T2DM). SFlt-1 and PlGF were clearly increased in HF patients in comparison to T2DM patients or healthy subjects ( p  < 0.01). Concentration of sFlt-1 was related to HF severity ( p  < 0.001) and was correlated to NT-proBNP ( ρ   = 0.37, p  < 0.01), soluble ST2 ( ρ   = 0.52, p  < 0.01), Galectin-3 ( ρ   = 0.38, p  < 0.01), aldosterone ( ρ   = 0.25, p   = 0.01) and PTH(1–84) ( ρ   = 0.38, p  < 0.01). Furthermore, sFlt-1 levels were associated to long-term CV risk. These results suggest a potential role of sFlt-1 in HF and its potential role as biomarker of CV risk.